Phosphorus accumulation in Proteaceae seeds: a synthesis - Groom, Philip; Lamont, Byron (2009)
The family Proteaceae dominates the nutrient-poor, Mediterranean-climate floristic regions of southwestern Australia (SWA) and the Cape of South Africa. It is well-recognised that mediterranean Proteaceae have comparatively large seeds that are enriched with phosphorus (P), stored mainly as salts of phytic acid in protein globoids. Seed P can contribute up to 48% of the total aboveground P, with the fraction allocated depending on the species fire response. For SWA species, 70–80% of P allocated to fruiting structures is invested in seeds, compared with 30–75% for Cape species, with SWA species storing on average 4.7 times more P per seed at twice the concentration. When soil P is less limiting for growth, seed P reserves may be less important for seedling establishment, and hence plants there tend to produce smaller seeds with less P. For Australian Hakea and Grevillea species the translocation of P from the fruit wall to the seed occurs in the days/ weeks before final fruit dry mass is reached, and accounts for 4–36% of seed P. Seed P content increases with the level of serotiny, though it decreases marginally as a fraction of the total reproductive structure. The greater occurrence of serotiny and higher seed P content within the Proteaceae in SWA supports the notion that SWA soils are more P-impoverished than those of the Cape.